Refleksi Terhadap Makna Keadilan Sebagai Fairness Menurut John Rawls Dalam Perspektif Keindonesiaan - Fadhilah, Fadhilah (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2012)
Justice contains a universal moral values of which is a basic human right and all over the world, as well as with the Indonesian nation, social justice ideals and objectives of Indonesia as stated in the Preamble to the Constitution of 1945 Alenia fourth. But in the application of the universal values of justice, there are several different principles of justice between one to understand that theories. But in the application of the universal values of justice, there are several different principles of justice to understand. This literature study raised the theory of justice John Rawls's principle of